NILAI-NILAI PAI MULTIKULTURAL DI PIAUD (Tinjauan Epistemologi) - Rosichin Mansur (Jurnal Dewantara, 2021)
Multicultural Islamic education teaches people to be aware of and understand the diversity in life on earth. Diversity is basically sunatullah, so that humans must recognize, accept and appreciate the differences in equality. Difference as something beautiful, not the embryo of hostility or division. Multicultural Islamic education as education that carries the values of divinity and humanity, which decomposes into the values of peace, freedom, wisdom, tasamuh, tawazun, taawun, tawasuth, pluralism, and inclusiveness. These values are actualized in Islamic education at various existing levels, one of which is actualized in early childhood Islamic education in a fun play package.